A Gate-to-gate Case Study of the Life Cycle Assessment of an Oil Palm Seedling - Halimah Muhamad; Ismail Bin Sahid; Salmijah Surif; Tan Yew Ai; Choo Yuen May (Tropical Life Sciences Research, 2012)
The palm oil industry has played an important role in the economic development of Malaysia and has enhanced the economic welfare of its people. To determine the environmental impact of the oil palm seedling at the nursery stage, information on inputs and outputs need to be assessed. The oil palm nursery is the first link in the palm oil supply chain. A gate-to-gate study was carried out whereby the system boundary was set to only include the process of the oil palm seedling. The starting point was a germinated seed in a small polyethylene bag (6 in x 9 in) in which it remained until the seedling was approximately 3 to 4 months old. The seedling was then transferred into a larger polyethylene bag (12 in x 15 in), where it remained until it was 10–12 months old, when it was planted in the field (plantation). The functional unit for this life cycle inventory (LCI) is based on the production of one seedling. Generally, within the system boundary, the production of an oil palm seedling has only two major environmental impact points, the polybags used to grow the seedling and the fungicide (dithiocarbamate) used to control pathogenic fungi, as both the polybags and the dithiocarbamate are derived from fossil fuel. Industri minyak sawit memainkan peranan yang penting di dalam pembangunan ekonomi Malaysia dan telah meningkatkan kebajikan ekonomi rakyat. Untuk menentukan impak alam sekitar bagi anak pokok sawit di peringkat nurseri, maklumat mengenai input dan output perlu dinilai. Nurseri sawit merupakan rangkaian pertama dalam rantaian bekalan minyak sawit. Kajian gate-to-gate telah dijalankan di mana sempadan sistem telah ditetapkan untuk memasukkan hanya proses anak pokok sawit. Titik permulaan bagi proses ini adalah biji benih cambah sawit, disemai di dalam beg polietilena kecil (6 in x 9 in) dan dibiarkan sehingga anak pokok mencapai 3 hingga 4 bulan. Kemudian, anak pokok itu akan dipindahkan ke dalam beg polietilena yang lebih besar (12 in x 15 in) dan dibiarkan sehingga anak pokok mencapai 10–12 bulan, sebelum anak pokok itu ditanam di ladang. Unit fungsi bagi inventori kitaran hayat (LCI) adalah berdasarkan penghasilan satu anak pokok sawit. Secara amnya, dalam sempadan sistem, penghasilan anak pokok sawit hanya mempunyai dua impak alam sekitar yang utama iaitu polibeg yang digunakan semasa penanaman anak pokok dan juga racun kulat (ditiokarbamat) yang digunakan untuk mengawal kulat patogen, yang mana kedua-dua polibeg dan ditiokarbamat diperolehi dari bahan api fosil.